2000
DOI: 10.1093/toxsci/55.1.143
|View full text |Cite
|
Sign up to set email alerts
|

Dose-Dependent Alterations in Androgen-Regulated Male Reproductive Development in Rats Exposed to Di(n-butyl) Phthalate during Late Gestation

Abstract: Di(n-butyl) phthalate (DBP) is a commercially important plasticizer and ubiquitous environmental contaminant. Since previous, limited dose-response studies with DBP that reported alterations in male reproductive development and function failed to establish a NOAEL (no-observed-adverse-effect level), an extensive dose-response study was conducted. Pregnant CD rats were given DBP by gavage at 0, 0.5, 5, 50, or 100 mg/kg/day (n = 19-20) or 500 mg/kg/day (n = 11) from gestation day 12 to 21. In male offspring, ano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
293
1
7

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 418 publications
(314 citation statements)
references
References 31 publications
13
293
1
7
Order By: Relevance
“…FLCs were aggregated rather than dispersed when doses of DEHP were increased. Previous studies similarly reported that high-dose exposures to DEHP or DBP in utero resulted in focal disruptions in the structure of the seminiferous epithelium and in abnormal aggregations of FLCs (24,25). Stereological analyses have suggested that the increased FLC number per cluster in response to DEHP does not result from increased Leydig cell numbers (our results and ref.…”
Section: Resultssupporting
confidence: 84%
“…FLCs were aggregated rather than dispersed when doses of DEHP were increased. Previous studies similarly reported that high-dose exposures to DEHP or DBP in utero resulted in focal disruptions in the structure of the seminiferous epithelium and in abnormal aggregations of FLCs (24,25). Stereological analyses have suggested that the increased FLC number per cluster in response to DEHP does not result from increased Leydig cell numbers (our results and ref.…”
Section: Resultssupporting
confidence: 84%
“…gestation day (GD) 12-19, results in remarkable phenotypic alterations in normal development. 63,64 At adulthood the phenotypes included: cryptorchidism, epididymal agenesis, testicular atrophy with germ cell loss, hypospadias, and absent or smaller seminal vesicles and prostate. These phenotypes can be linked to androgen deprivation during the critical period of sexual differentiation.…”
Section: -62mentioning
confidence: 99%
“…and Rodgers and Rowland4 are listed in Table 2 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40…”
Section: Resultsmentioning
confidence: 99%